Factors influencing science content accuracy in elementary inquiry science lessons - Nowicki, Barbara L.; Sullivan-Watts, Barbara; Shim, Minsuk K.; Young, Betty; Pockalny, Robert (Research in science education (Australasian Science Education Research Association), 2013)
Elementary teachers face increasing demands to engage children in authentic science process and argument while simultaneously preparing them with knowledge of science facts, vocabulary, and concepts. This reform is particularly challenging due to concerns that elementary teachers lack adequate science background to teach science accurately. This study examined 81 in-classroom inquiry science lessons for preservice education majors and their cooperating teachers to determine the accuracy of the science content delivered in elementary classrooms. Results showed that 74 % of experienced teachers and 50 % of student teachers presented science lessons with greater than 90 % accuracy. Eleven of the 81 lessons (9 preservice, 2 cooperating teachers) failed to deliver accurate science content to the class. Science content accuracy was highly correlated with the use of kit-based resources supported with professional development, a preference for teaching science, and grade level. There was no correlation between the accuracy of science content and some common measures of teacher content knowledge (i.e., number of college science courses, science grades, or scores on a general science content test). This study concluded that when provided with high quality curricular materials and targeted professional development, elementary teachers learn needed science content and present it accurately to their students. [Author abstract, ed]